Investigation of syngas combustion at variable methane composition in can combustor using CFD - Zian N.M.; Hasini H.; Om N.I. (Trans Tech Publications Ltd, 2023)
This paper describes the analysis of the fundamental effect of synthetic gas combustion in a can-type combustor using Computational Fluid Dynamic(CFD). Emphasis is given towards the effect of variation of methane to the flame profile, temperature distribution and heat flux in the combustor. In this study, the composition of hydrogen in the syngas was fixed at 30% while methane and carbon monoxide were varied. Results show that the flame temperature and NOx emissions are highly dependent on the composition of methane in the syngas fuel. Nevertheless, the overall NOx emission for all cases is relatively lower than the conventional pure natural gas combustion. © (2014) Trans Tech Publications, Switzerland.